Correlations Between Social and National Mobility in Carniola - PREINFALK, Miha (Studia Universitatis Babeș-Bolyai Historia, 2024)
The article provides a brief overview of the position of the nobility in Slovenia. First, it focuses on the connection between the nobility and historiography, which from the mid-19th century was increasingly burdened by the national struggles of the past. The findings show that until the mid-19th century the nobility was strongly integrated into Slovenian society, including through the use of the Slovene language, but was then forced into a national definition, and as a rule (with few exceptions) chose to take the German side. More than a change in ethnic identity, a change in social identity was relevant in the early modern period. The new nobility tried as much as possible to adopt and take on a manner of behaviour that suited to their new status. This especially meant the purchase of landed property and forming kinship ties with other noble families. The article concludes with a brief overview of the fate of the nobility in Slovenia after 1918. Rezumat. Articolul oferă o scurtă prezentare a situaţiei nobilimii în Slovenia. În primul rând, se concentrează asupra legăturii dintre mibilime şi istoriografie, care de la mijlocul secolului al XIX-lea a fost din ce în ce mai mult marcată de luptele naţionale ale trecutului. Concluziile arată că, până la jumătatea secolului al XIX-lea, nobilimea a fost puternic integrată în societatea slovenă, inclusiv prin utilizarea limbii slovene, dar apoi a fost forţată să se definească la nivel naţional şi, de regulă (cu câteva excepţii), a optat pentru o identitate germană. Mai mult decât o schimbare a identităţii etnice, o schimbare a identităţii sociale a fost de asemenea relevantă în perioada modernă timpurie. Noua nobilime a încercat pe cât posibil să adopte şi să preia un mod de comportament adecvat noului lor statut. Acest lucru a însemnat în special achiziţionarea de proprietăţi funciare şi formarea de legături de rudenie cu alte familii nobile. Articolul se încheie cu o scurtă trecere în revistă a sorţii nobilimii din Slovenia după 1918. Cuvinte-cheie: Nobilime, Slovenia, mişcare naţională, istoriografie, etnie, mobilitate socială Article: history; Received: 12.12.2023; Revised: 23.12.2023 Accepted: 29.12.2023; Available online: 30.01.2024